Analisis Struktural dan Moral Cerpen “Pulang” Karya Marliana Kuswanti - Fitriani, Assyva; Abdurahman, Abdurahman (Lembaga Yasin AlSys, 2026)
A study of the short story Pulang by Marlina Kuswanti is important to reveal the relationship between the intrinsic elements and the moral message constructed in the text. This study aims to analyze the short story Pulang by Marlina Kuswanti through a structural approach and a moral approach. Structurally, the analysis focuses on the intrinsic elements of the short story, which include character and characterization, plot, setting, point of view, language style, and message, all of which form the thematic unity of Apin’s childhood trauma. Morally, this study discusses the impact of family dysfunction that affects the psychological condition of the main character as well as the decline in ethics caused by the struggle over inheritance. This study employed a qualitative method with literature study techniques and content analysis. The results show that, structurally, the author employs the symbolic comparison of “cold” and “hot” to represent the childhood trauma experienced by Apin. Meanwhile, morally, the results show that human values have declined because a toxic family environment creates social alienation for family members. This study concludes that the context of “returning home” in this short story does not represent home as a comfortable place, but rather as a source of trauma. These findings affirm that structural and moral readings can broaden understanding of the representation of trauma, family relations, and the degradation of human values in literary works.